The Effect of Shadowing Technique in Teaching Speaking at A University - Rosyidi, Ahmad Zuhri; Masyudi, Masyudi; Paris, Atika Salman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aimed to know the extent effect of the shadowing technique in developing students' abilities at Institut Pendidikan Nusantara Global. The method used in this study is quasi-experiment, involving two classes as the experiment class. The sample consists of 78 students in the third (3rd) semester. The data collection techniques used are observation sheets and audio tests that must be followed by students. The result of this study then calculates utilizing SPSS to know the difference between the Pre-Test and Post-Test. The result of this study shows that there is an effect of the shadowing technique on students' speaking ability at Institut Pendidikan Nusantara Global. It can be proved by the result of the hypothesis test, which showed a significant level of 0.000, which means <0.05. Thus, it can be concluded that Ha was accepted and Ho was rejected.